Proposition d’un modèle d’éducation à la consommation au secondaire - Adolfo Agundez Rodriguez; Ghislain Samson; France Jutras (VertigO, 2008)
Consumer education is part of the transversal contents of the Quebec high school education program (MEQ, 2004; MELS, 2007a et b). Although there are several ways to integrate consumer education into the curriculum, the Ministry provides few means for  its practical application (CSE, 2007). Therefore, the consumer education model for high school presented in this article contains elements that support the reflection about consumption, the type of society thus being generated and the consumer behaviour it entails. The pedagogical purpose pursued by this model is to bring the students to adopt an ethical model of consumption based on a just, equitable consumption, in solidarity with other human beings, and oriented towards people welfare (Cortina, 2002).